2023
DOI: 10.1161/jaha.122.028999
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in the Use and Outcomes of Transcatheter Mitral Valve Replacement: Analysis From the National Inpatient Sample Database

Abstract: Background Racial and ethnic disparities in outcomes exist following many cardiac procedures. Transcatheter mitral valve replacement (TMVR) has grown as an alternative to mitral valve surgery for patients at high surgical risk. The outcomes of TMVR by race and ethnicity are unknown. We aimed to evaluate racial and ethnic disparities in the outcomes of TMVR. Methods and Results We analyzed the National Inpatient Sample database from 2016 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Studies have found that Black patients are less likely to undergo mitral valvuloplasty, especially when their disease is non-rheumatic in origin [ 13 ]. Hispanic are also less likely to receive mitral valve interventions, specifically Transcatheter Mitral Valve Replacement (TMVR), an important technique for patients at high open surgical risk [ 25 ]. Transcatheter Edge to Edge Repair (TEER) is a similarly important technique for high-risk patients.…”
Section: Literature Review and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that Black patients are less likely to undergo mitral valvuloplasty, especially when their disease is non-rheumatic in origin [ 13 ]. Hispanic are also less likely to receive mitral valve interventions, specifically Transcatheter Mitral Valve Replacement (TMVR), an important technique for patients at high open surgical risk [ 25 ]. Transcatheter Edge to Edge Repair (TEER) is a similarly important technique for high-risk patients.…”
Section: Literature Review and Resultsmentioning
confidence: 99%
“…[ 4 , 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 19 ]) and Table 2 (Ref. [ 12 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]) below.…”
Section: Discussionmentioning
confidence: 99%
“…14 Similar to prior NIS studies, three racial/ethnic groups with small sample sizes (Asian or Pacific Islander, Native American, and other) were combined into a single ‘other’ group to facilitate the analysis. 15–17 The other three HCUP racial/ethnic groups (White, Black, and Hispanic) were left unchanged for the study. The ‘White’ group refers to non-Hispanic White patients, the ‘Black’ group refers to non-Hispanic Black patients, and the ‘Hispanic’ group refers to Hispanic patients of all races and origins.…”
Section: Methodsmentioning
confidence: 99%
“…15 This method was similar to other studies analyzing racial and ethnic disparities among different disease processes and their treatments. 17 , 18 , 19 , 20 , 21 , 22 …”
Section: Methodsmentioning
confidence: 99%